2021
DOI: 10.1021/jacs.1c06192
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation of High Mobility Group Box 1 (HMGB1) Alters Its DNA Binding and DNA Damage Processing Activities

Abstract: Protein O-GlcNAcylation is an essential and dynamic regulator of myriad cellular processes, including DNA replication and repair. Proteomic studies have identified the multifunctional nuclear protein HMGB1 as O-GlcNAcylated, providing a potential link between this modification and DNA damage responses. Here, we verify the protein’s endogenous modification at S100 and S107 and found that the major modification site is S100, a residue that can potentially influence HMGB1-DNA interactions. Using synthetic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“… 79 We also used these techniques to study the effect of O-GlcNAcylation on semisynthetic HMGB1 modified at positions Ser100 and demonstrated the influence O-GlcNAc has on HMGB1-DNA interactions. 80 We showed that the PTM generally enhanced the interactions between the protein and DNA and resulted in error-prone repair of ICL-damaged plasmids in U2OS cell extracts. Finally, we have also studied the effect of O-GlcNAc modifications of small heat shock proteins (sHSPs) using NCL and EPL methods.…”
Section: O-glcnac Modulation: Chemical Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“… 79 We also used these techniques to study the effect of O-GlcNAcylation on semisynthetic HMGB1 modified at positions Ser100 and demonstrated the influence O-GlcNAc has on HMGB1-DNA interactions. 80 We showed that the PTM generally enhanced the interactions between the protein and DNA and resulted in error-prone repair of ICL-damaged plasmids in U2OS cell extracts. Finally, we have also studied the effect of O-GlcNAc modifications of small heat shock proteins (sHSPs) using NCL and EPL methods.…”
Section: O-glcnac Modulation: Chemical Methodsmentioning
confidence: 86%
“…We further showed that the PTM is protective against the protein’s cleavage by calpain, and that the anti-aggregation phenotypes imparted by the GlcNAc moiety are unique and not reproduced by other sugars . We also used these techniques to study the effect of O-GlcNAcylation on semisynthetic HMGB1 modified at positions Ser100 and demonstrated the influence O-GlcNAc has on HMGB1-DNA interactions . We showed that the PTM generally enhanced the interactions between the protein and DNA and resulted in error-prone repair of ICL-damaged plasmids in U2OS cell extracts.…”
Section: O-glcnac Modulation: Chemical Methodsmentioning
confidence: 94%
“…Amino acids conducive to maintaining an extended or random coil structure significantly affect the propensity of a peptide to be glycosylated and may explain the preference for prolines and beta-branched residues(2). Although the vast majority of OGT substrates are in IDRs(5), there are a few examples of proteins that are glycosylated in folded or ordered regions, including HBGB-1(74), H2B(75) and αB-Crystallin(76). Glycosylation of these ordered sites could occur if the TPR is able to move away from the catalytic site, as has been suggested by a recent electron microscopy structure(77).…”
Section: Discussionmentioning
confidence: 99%
“…During DNA synthesis, flap endonuclease 1 (FEN1) is O-GlcNAcylated and the abrogation of which will lead to DNA damage accumulation (12). Furthermore, High mobility group B1 (HMGB1) is O-GlcNAcylated, which alters its DNA binding ability and promotes an error-prone DNA repair (13). Recently, WD repeat and HMG-box DNA-binding protein 1 (WDHD1/AND-1) is also shown to be O-GlcNAcylated and takes part in HR (14).…”
Section: Introductionmentioning
confidence: 99%